Equilibrium moisture contents and sorption isotherms of Amorphophallus konjac tuber slices - Syamsinar Rahmia; Junaedi Muhidong; Salengke; Amran Laga (Hasanuddin University Food Science and Technology Study Program, 2022)
Amorphophallus konjac fresh tubers are often used as a raw material for making food because it has a fairly high nutritional content. Therefore, it is very important to measure the equilibrium moisture content of fresh andprocessed tuber. The present study aimed to determine the best model to represent the equilibrium moisture content for adsorption and desorption isotherms of Amorphophallus konjac tuber slices. The tuber samples weresliced into slices (3.0 × 3.0 × 0.8 cm) and rinsed in a 0.2% salt solution for approximately 2 min. Half of the samples were blanched in water bath at 80⁰C for 5 min. The samples (blanched (B) and non-blanched (NB)) wereplaced into 6 desiccators containing salt solution with relative humidity of 17%–82%. The desiccators were stored at constant temperatures of 30⁰C (room temperature) and 40⁰C. Three models were comparatively evaluatedin this study: the Henderson, Oswin, and Chung–Pfost. Excel Solver was applied to determine the value of each parameters in the models. The water sorption isotherms type was sigmoidal, indicating the closed relationship between the single layer area of relative humidity samples with the equilibrium moisture content. Based on the magnitudes of coefficient of determination (R²), root mean squared error (RMSE), and Chi-square (χ²) value the Oswin and Chung–Pfost models were found to be the best-fitted models to represent the equilibrium moisture content of A. konjac tuber slices at storage temperatures of 30⁰C and 40⁰C, respectively